Are GPCRs Still a Source of New Targets? - Garland, Stephen L. (Journal of biomolecular screening, 2013)
G-protein-coupled receptors (GPCRs) still offer enormous scope for new therapeutic targets. Currently marketed agents are dominated by those with activity at aminergic receptors and yet they account for only ~10% of the family. Progress up until now with other subfamilies, notably orphans, Family A/peptide, Family A/lipid, Family B, Family C, and Family F, has been, at best, patchy. This may be attributable to the heterogeneous nature of GPCRs, their endogenous ligands, and consequently their binding sites. Our appreciation of receptor similarity has arguably been too simplistic, and screening collections have not necessarily been well suited to identifying leads in new areas. Despite the relative shortage of high-quality tool molecules in a number of cases, there is an emerging, and increasingly substantial, body of evidence associating many as yet "undrugged" receptors with a very wide range of diseases. Significant advances in our understanding of receptor pharmacology and technical advances in screening, protein X-ray crystallography, and ligand design methods are paving the way for new successes in the area. Exploitation of allosteric mechanisms; alternative signaling pathways such as G12/13, Gβγ, and β-arrestin; the discovery of "biased" ligands; and the emergence of GPCR-protein complexes as potential drug targets offer scope for new and much improved drugs.